Are web-based stress management interventions effective as an indirect treatment for depression? An individual participant data meta-analysis of six randomised trials - Harrer, Mathias; Nixon, Patricia; Sprenger, Antonia A.; Heber, Elena; Boß, Leif; Heckendorf, Hanna; Buntrock, Claudia; Ebert, David Daniel; Lehr, Dirk (BMJ Mental Health, 2024)
QUESTION: Depression is highly prevalent and associated with numerous adverse consequences for both individuals and society. Due to low uptake of direct treatment, interventions that target related, but less stigmatising problems, such as perceived stress, have emerged as a new research paradigm.This individual participant data (IPD) meta-analysis examines if a web-based stress management intervention can be used as an 'indirect' treatment of depression. STUDY SELECTION AND ANALYSIS: Bayesian one-stage models were used to estimate pooled effects on depressive symptom severity, minimally important improvement and reliable deterioration. The dose-response relationship was examined using multilevel additive models, and IPD network meta-analysis was employed to estimate the effect of guidance. FINDINGS: In total, N=1235 patients suffering from clinical-level depression from K=6 randomised trials were included. Moderate-to-large effects were found on depressive symptom severity at 7 weeks post-intervention (d=-0.65; 95% credibility interval (CrI): -0.84 to -0.48) as measured with the Center for Epidemiological Studies' Depression Scale. Effects were sustained at 3-month follow-up (d=-0.74; 95% CrI: -1.01 to -0.48). Post-intervention symptom severity was linearly related to the number of completed sessions. The incremental impact of guidance was estimated at d=-0.25 (95% CrI: -1.30 to 0.82), with a 35% posterior probability that guided and unguided formats produce equivalent effects. CONCLUSIONS: Our results indicate that web-based stress management can serve as an indirect treatment, yielding effects comparable with direct interventions for depression. Further research is needed to determine if such formats can indeed increase the utilisation of evidence-based treatment, and to corroborate the favourable effects for human guidance. STUDY REGISTRATION: Open material repository: osf.io/dbjc8, osf.io/3qtbe. TRIAL REGISTRATION NUMBER: German Clinical Trial Registration (DRKS): DRKS00004749, DRKS00005112, DRKS00005384, DRKS00005687, DRKS00005699, DRKS00005990.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Adult psychiatry; Depression & mood disorders